Ad-hoc Networks and Wireless : ADHOC-NOW 2014 International Workshops, ETSD, MARSS, MWaoN, SecAN, SSPA, and WiSARN, Benidorm, Spain, June 22--27, 2014, Revised Selected Papers - Garcia Pineda, Miguel; Lloret, Jaime; Papavassiliou, Symeon; Ruehrup, Stefan; Westphall, Carlos Becker; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of six workshops collocated with the 13th International Conference on Ad-Hoc Networks and Wireless, ADHOC-NOW Workshops 2014, held in Benidorm, Spain, in June 2014. The 25 revised full papers presented were carefully reviewed and selected from 59 submissions. The papers address the following topics: emerging technologies for smart devices; marine sensors and systems; multimedia wireless ad hoc networks; security in ad hoc networks; smart sensor protocols and algorithms; wireless sensor, actuator and robot networks.
Emerging technologies for smart devices -- Marine sensors and systems -- Multimedia wireless ad hoc networks -- Security in ad hoc networks -- Smart sensor protocols and algorithms -- Wireless sensor, actuator and robot networks.
Keywords: Computer Communication Networks; Telecommunication; Information Systems; Software engineering; Information storage and retrieva; Computer Communication Networks; Information Systems Applications (incl. Internet).; Communications Engineering, Networks; Management of Computing and Information Systems; Software Engineering; Information Storage and Retrieval